PENGARUH MINAT WIRAUSAHA DAN SELF EFFICACY TERHADAP KINERJA UMKM DI BENGKAYANG - Eligia Monixa Salfarini; Dedy; Yeremia Niaga Atlantika; Sabinus Beni; Maya Sari (POLITEKNIK LP3I JAKARTA, 2025)
Performance is an important thing that must be considered in the growth of Small and Micro Enterprises (MSMEs). This study aims to identify and analyze the effect of entrepreneurial interest and self-efficacy on the performance of MSMEs in Bengkayang City. This research is quantitative research with a survey approach. Questionnaires were used in collecting data on 58 MSME players in Bengkayang City who were included in the culinary, service, basic food and clothing businesses. The variables studied included entrepreneurial interest, self efficacy and MSME performance. The data analysis technique uses multiple regression tests using SPSS as an analytical tool to determine the effect of entrepreneurial interest and self efficacy on MSME performance. The results showed that entrepreneurial interest had no effect on performance while self efficacy had a positive effect on performance. The results also showed that entrepreneurial interest and self efficacy together had an effect on the performance of MSMEs in Bengkayang City. The higher the entrepreneurial interest and self efficacy, the higher the performance of MSMEs.